EVALUASI PENGELOLAAN SAMPAH MEDIS DI RSUD KOTA TANGERANG - Pramiati Purwaningrum; Dwi Indrawati; Hernani Yulinawati (Jurnal Lingkungan dan Kota, 2021)
Health care facilities produce medical solid waste such as household waste and waste categorized as medical waste as well as large amounts of hazardous and toxic waste (B3). From the risks posed, the solid waste produced by health care facilities which is non-medical waste, namely household waste does not contain risks, the amount is around 70-90%. While the remaining 10-25% is waste that can cause various health impacts because it is considered dangerous. The purpose of this study is to investigate the risks that can arise from the waste generated by health care facilities and to evaluate the waste management of health agencies. The stages of this research include preparation, literature review, data collection both primary and secondary data, data analysis, and data evaluation. The occurrence of the COVID-19 pandemic at the end of 2019 to 2020 resulted in a significant increase in the generation of medical waste at the Tangerang City General Hospital by 77.1%. Transportation of B3 waste by third parties is hampered because the amount of solid medical waste has increased in the COVID-19 pandemic.